Museum of capitalism - Linke, Rosa 1977- (Inventory Press, 2017)
The Museum of Capitalism in Oakland, California, treats capitalism as a historical phenomenon. This speculative institution views the present and recent past from the implied perspective of a future society in which our economic and political system is memorialized, and subjected to the museological gaze. Sketches and renderings of exhibits and artifacts, combined with relevant quotations from historical sources, are interspersed with speculative essays on the intersections of ecology, race, museology, historiography, economics and politics
Literaturverzeichnis Seite 166. - "Produced on the occasion of the exhibition in Oakland, CA from June 17-August 20, 2017"
Keywords: Kunst; Kapitalismus -- Motiv; Politik -- Motiv; Capitalism / In art / Exhibitions; Politics in art / Exhibitions; Ausstellungskatalog -- Museum of Capitalism -- 17.06.2017-20.08. 2017 -- Oakland, Calif.